The antioxidant, anti-inflammatory and antiplatelet effects of Ribes rubrum L. fruit extract in the diabetic rats - ŞENER, AZİZE; ŞEKERLER, TURGUT; ŞEN, ALİ (My University, 2022)
AbstractThe prothrombotic and inflammatory state plays a significant role in the occurrence of cardiovascular complications in type 2 diabetes mellitus. In this study, the antidiabetic, anti-inflammatory, and antiplatelet potentials of the extracts obtained fromRibes rubrumwere investigated. The antidiabetic, anti-inflammatory, and antioxidant activities of the ethanol and water extracts ofR. rubrumwere evaluated by in vitro methods. The total phenolic and flavonoid contents were also determined. The experimental diabetes model in rats was induced with streptozotocin (STZ). After hyperglycemia occurred, the ethanol extracts ofR. rubrum(RRE, at 100mg/kg and 500mg/kg doses) were administered to the treatment groups for 14days. Blood glucose, lipid profile, plasma, and pancreas tumor necrosis factor-α (TNF-α) levels were determined and compared at the end of the experiments. P-selectin levels and mitochondrial membrane polarization (MMP) of platelets were also measured. In vitro study, the RRE showed potent anti-inflammatory activity. Administration of RRE (at 100mg/kg doses) to diabetic rats lowered blood glucose level insignificantly. The results showed that there was an increment in levels of TNF-α in plasma and pancreas tissue of the diabetic group compared to the control group.R. rubrumextract regulated and normalized their levels in plasma and pancreatic tissue. RRE at both doses significantly decreased platelet P-selectin levels and prevented STZ-induced loss of MMP in platelets. The results of current research indicate that RRE extract has potent anti-platelet and anti-inflammatory effects and may be beneficial in preventing diabetic complications.Practical applicationsHyperglycemia causes dyslipidemia, advanced oxidative stress, platelet activation, and inflammation in diabetes mellitus. Plants with various medicinal properties are of worldwide interest for the treatment of diseases due to their biological activities. In this study, the antidiabetic, anti-inflammatory, and antioxidant effects of extracts ofRibes rubrum(%100 ethanol, 50% ethanol, water) were evaluated by in vitro and in vivo methods. The diabetes model was induced with streptozotocin (STZ). The rats were divided into control, diabetic control,R. rubrum-100mg/kg, andR. rubrum-500mg/kg doses groups. Blood glucose levels, tumor necrosis factor-α (TNF-α), platelet P-selectin levels, mitochondrial membrane polarization of platelets were examined. The present study has shown thatR. rubrumhas anti-inflammatory and antiplatelet activity.R. rubrummay be beneficial in the prevention and treatment of DM complications due to its anti-inflammatory and antithrombotic effects.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)